A reestruturação do setor de telecomunicações no Brasil: os caminhos da privatização e os desafios do aprendizado institucional da regulação - Cardoso, Jucyene das Graças (2000)
The opening up of the telecommunications sector in Brazil to the participation of private capital, and the privatization of public operators in July 1998, introduced the presence of new social actors in the sector, potentiating the emergence of conflicts between new and old actors, with their respective competition strategies. The State moves from the function of direct provider of telecommunications services to that of regulatory agent via the regulatory agency: Anatel - Agência Nacional de Telecomunicações. Since the country had no experience with this new regulation and inspection mechanism for the telecommunications sector, previously these functions were limited to the scope of the Ministry of Communications, the State's performance through Anatel presents itself as a challenge to public action, as well as the actors involved in the sector, consumers and suppliers. In this sense, the work presented the model of privatization and regulation adopted in Brazil and, more specifically, investigated the challenges posed to the country in the institutional learning of regulation via the regulatory agency. For that, Anatel became the object of analysis of the work. The research undertaken reveals the great challenge posed to Anatel, whether in the inspection of the sector, or in guaranteeing the rights of users, or in the universalization of services and in promoting conditions for greater technological qualification in the country. These challenges take on relevant proportions when one takes into account the great power of the international operators installed here, the enormous concentration of income that marks this country, as well as the deep regional diversities of this continental country, in which the poorest and most remote areas are not. would be in the interests of large operators. Since the sector's regulatory agency, Anatel, represents a new space for the negotiation of interests between the public and private spheres, the research detected the great challenge of society in participating inside the Agency and, therefore, in defining the direction of the sector.